Elephantiasis nostras verrucosa in a patient with lipedema and lipolymphedema - Lívia Maria Pereira de Godoy; Paula Pereira de Godoy Capeletto; Ana Carolina Pereira de Godoy; ose Maria Pereira de Godoy (Our Dermatology Online, 2021)
Elephantiasis nostras verrucosa is a group of rare cutaneous changes comprising dermal fibrosis, hyperkeratotic, and verrucous and papillomatous lesions secondary to chronic non-filarial lymphedema. The following study reports a case associated with lipedema and lymphedema, several episodes of erysipelas unfolding over the previous years, and warty lesions appearing in the transitional region between the right ankle and foot. Several episodes of erysipelas in patients with lipolymphedema can evolve into elephantiasis nostras verrucosa (ENV).